Sistem Manajemen Penggunaan Alat Pelindung Diri (APD) Unit Radiologi RSU Efarina Etaham Pematang Siantar - Pelawi, Awan; Purba, Yeni Trisna; Purba, Eka Anastasya; Purba, Siska Gracia Oktafiana (3031-8572, 2022)
Radiation Safety and Health in the Utilization of Ionizing Radiation, hereinafter referred to as radiation safety, is an effort undertaken to create conditions such that the effects of ionizing radiation on humans and the environment do not exceed the determined threshold values. This study aims to examine the implementation of the Personal Protective Equipment (PPE) management system in the Radiology Unit at Efarina Etaham General Hospital, Pematangsiantar, and to provide insights and information for radiology workers regarding the PPE management system in the radiology unit. This research is descriptive in nature, utilizing a checklist measurement tool administered to two radiology workers. Based on the research conducted in the Radiology Unit at Efarina Etaham General Hospital, Pematangsiantar, regarding the Personal Protective Equipment Usage Management System, it can be concluded that radiology workers have not been using all the required PPE as mandated for a Class C hospital, such as Lead Aprons, Lead Glasses, Face Shields, Gloves, and other protective equipment. Therefore, it is recommended that the hospital management provide the necessary PPE for workers to use in carrying out their duties